(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article highlights the relevance of using a dietary iron-containing supplement based on heme iron for the development of energy bars with anti-anemic properties. The objective, object, and subject of the study are defined. The results of research on the physicochemical and functional-technological properties of raw materials used for the production of energy bars with anti-anemic properties are presented. Rational concentrations of formulation components have been established, and a production technology for energy bars based on a dietary iron-containing supplement has been developed. The chemical composition of the developed energy bars was investigated. The obtained results indicate that the developed energy bars surpass control samples in the content of most nutrients. In particular, the iron content increases by 1.27–1.29 times, other micro- and macroelements by 1.52±0.75%, vitamins by 1.36±0.41%, proteins by 1.16–1.18 times, and ash content, indicating a balanced nutrient composition of the final product. Microbiological studies confirm that the experimental samples comply with regulatory standards during 75 days of storage. It has been proven that the optimal content of the dietary iron-containing supplement at a level of 3.0% of the formulation mixture ensures high nutritional value, stability of physicochemical properties, and compliance with sanitary and microbiological standards. The addition of 3.0% of the iron-containing supplement reduces the risk of microbial contamination due to its antibacterial properties.